Accuracy and Safety of Pedicle Screw Placement in Adolescent Idiopathic Scoliosis Patients: A Review of 2020 Screws Using Computed Tomography Assessment. Issue 5 (March 2017) - Kwan, Mun Keong; Chiu, Chee Kidd; Gani, Siti Mariam Abd; Wei, Chris Chan Yin
Abstract : Study Design: Retrospective review of CT scan. Objective: To investigate the accuracy and safety of pedicle screws placed in adolescent idiopathic scoliosis (AIS) patients. Summary of Background Data: The reported pedicle screws perforation rates for corrective AIS surgery vary widely from 1.2% to 65.0%. Knowledge regarding the safety of pedicle screws in scoliosis surgery is very important in preventing complications. Methods: This study investigates the accuracy and safety of pedicle screws placed in 140 AIS patients. CT scans were used to assess the perforations that were classified according to Rao et al (2002): grade 0, grade 1 (<2 mm), grade 2 (2–4 mm), and grade 3 (>4 mm). Anterior perforations were classified into grade 0, grade 1 (<4 mm), grade 2 (4–6 mm), and grade 3 (>6 mm). Grade 2 and 3 (excluding lateral grade 2 and 3 perforation over thoracic vertebrae) were considered as critical perforations. Results: A total of 2020 pedicle screws from 140 patients were analyzed. The overall total perforation rate was 20.3% (410 screws) with 8.2% (166 screws) grade 1, 2.9% (58 screws) grade 2 and 9.2% (186 screws) grade 3 perforations. Majority of the perforations was because of lateral perforation occurring over the thoracic region, as a result of application of extrapedicular screws at this region. When the lateral perforations of the thoracic region were excluded, the perforation rate was 6.4% (129 screws), grade 2, 1.4% (28 screws) and grade 3, 0.8% (16 screws). There were only two symptomatic left medial grade 2 perforations: one screw at T12 presented with postoperative iliac crest numbness and another screw at L2 presented with radicular pain that subsided with conservative treatment. There were six anterior perforations abutting the right lung, four anterior perforations abutting the aorta, two anterior perforations abutting the esophagus, and one abutting the trachea was noted. Conclusion: Pedicle screws insertion in AIS has a total perforation rate of 20.3%. After exclusion of lateral thoracic perforations, the overall perforation rate was 8.6% with a critical perforation rate of 2.2% (44/2020). The rate of symptomatic screw perforation leading to radicular symptoms was 0.1%. There was no spinal cord, aortic, esophageal, or lung injuries caused by malpositioned screws in this study. Level of Evidence: 4